Boosting Tef (Eragrostis tef (Zucc.) Trotter)) Yield through the Use of Different Inter-Row Spacing and Seeding Rates - Wolde Tasew; Abera Habte; Fanuel Laekemariam (Advances in Agriculture)
Tef is the major staple cereal crop in Ethiopia. Broadcast method of sowing and lack of site-specific seeding rates are among the major constraints of tef productivity. In this context, a field experiment was conducted with the aim of optimizing inter-row spacing and seed rates for better growth and yield of tef in southern Ethiopia. Treatments consisted of five levels of seed rates (2.5, 5, 7.5, 10, and 12.5 kg ha−1) and four inter-row spacing (15, 20, 25, and 30 cm) that were combined in factorial arrangement and laid out in a randomized complete block design with three replications. Phenology, growth, yield components, and yield data were collected. The results revealed that lodging, main panicle weight, biomass, and grain yield were significantly affected by the interaction effect of inter-row spacing and seed rates. Seed rate of 2.5 kg ha−1 at 20 cm inter-row spacing prolonged crop phonology, enhanced tiller formation, and increased panicle and 1,000-grain weight than other treatments. The maximum grain yield (2,400 kg ha−1) was obtained from the combination 2.5 kg ha−1 seed rate with 20 cm inter-row spacing. Taking the agronomic and economic advantages, it was concluded that a seed rate of 2.5 kg ha−1 with an inter-row spacing of 20 cm was suggested for tef growing farmers with similar agroecology of the study area.